ANALISIS PENGARUH BOPO, NPL, NIM, DAN LDR TERHADAP PROFITABILITAS PADA BANK UMUM DI INDONESIA PERIODE 2012-2017 - Evi Rohmiati; Winarni Winarni; Nina Woelan Soebroto (KEUNIS, 2019)
This research is performed in order to test the influence of the Operation Expenses to Operations Income (BOPO), Non Performing Loan (NPL), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) toward Profitability of Commercial Banks in Indonesia Period 2012-2017.             The sample used is 7 Commercial Banks that entered into the list of Commercial Banks Business Activities 2012-2017. The independent variables in this research are BOPO, NPL, NIM, and LDR. While the dependent variable is Profitability which is represented by Return On Assets (ROA). The analysis model used in this research is Multiple Linear Regression, while the analysis technique in this research using F Statistic Test, t Statistic Test, and Determination Coefficient Test.             The results of this research show that BOPO and NIM have significant influence to Profitability, while NPL and LDR have not significant influence to Profitability. Based on result of regression analysis, it is obtained that Adjusted R2 is 0,906, meaning the contribution of independent variable in explaining the dependent variable is 90,6% and the rest that is 9,4% is influenced by other variable not examined in this research.